The effect of irrigation procedures on the indicators of the white cabbage root system and the upper part of the earth - Nurmatov N.J; Alibekov T (Zien Journals, 2023)
Many studies have been conducted in the country on the development of elements of technology for the selection and cultivation of white cabbage varieties, and its promising varieties have been selected and other elements of planting time, planting schemes, and cultivation technology have been developed and widely introduced. But research on the cultivation of white cabbage through drip irrigation technology has hardly been carried out.
Keywords: White cabbage; cabbage; limited field wet capacity; soil moisture